2023
DOI: 10.1039/d3ra03838f
|View full text |Cite
|
Sign up to set email alerts
|

The potentials of boron-doped (nitrogen deficient) and nitrogen-doped (boron deficient) BNNT photocatalysts for decontamination of pollutants from water bodies

Abstract: This work investigates the structural, elastic, electronic, and photoabsorption properties of boron- (N-deficient) and nitrogen- (B-deficient) doped single-walled boron nitride nanotube (SWBNNT) for photocatalytic applications for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 33 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…It has also been reported that the photocatalytic performance of direct band gap materials can be improved through band gap modification which includes doping and defect engineering [8]. Itas et al, (2023) studied the photocatalytic efficiency of B-doped boron nitride nanotubes (BNNTs) using density functional theory [9]. Results revealed that B impurities could narrow the wide band gap of BNNT to the photocatalytic range of 2.3-2.8 eV.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the photocatalytic performance of direct band gap materials can be improved through band gap modification which includes doping and defect engineering [8]. Itas et al, (2023) studied the photocatalytic efficiency of B-doped boron nitride nanotubes (BNNTs) using density functional theory [9]. Results revealed that B impurities could narrow the wide band gap of BNNT to the photocatalytic range of 2.3-2.8 eV.…”
Section: Introductionmentioning
confidence: 99%